Synthesis of Cellulase during Abscission of Phaseolus vulgaris Leaf Explants - Lewis, L. N. (1970)
When abscission in leaf explants from Phaseolus vulgaris, cultivar Red Kidney, was allowed to proceed while the explants were in (2)H(2)O, a 1.25% increase in the buoyant density of cellulase in a cesium chloride gradient was observed. These data indicate that the increase in cellulase activity during abscission is a result of the synthesis of new protein. Two differentially soluble forms of cellulase are present in the abscission zone. The form which is soluble only in a high salt buffer seems more closely related to the abscission process than the form which is soluble in dilute buffer. The correlation between changes in pull force and increase in cellulase activity and the effects of several hormones on cellulase activity are discussed.